Mortality Rate of Geriatric Acetabular Fractures Is High Compared With Hip Fractures. A Matched Cohort Study. Issue 8 (August 2020) - Khoshbin, Amir; Atrey, Amit; Chaudhry, Hasaan; Nowak, Lauren; Melo, Luana T.; Stavrakis, Alexandra; Schemitsch, Emil H.; Nauth, Aaron
Abstract : Objectives: Compare acute complication and mortality rates of geriatric patients with acetabular fractures (AFs) matched to hip fractures (HFs). Design: Retrospective cohort study. Setting: American College of Surgeons National Surgical Quality Improvement Project. Patients: Using Current Procedural Terminology codes, the American College of Surgeons National Surgical Quality Improvement Project registry was used to identify all patients ≥60 years from 2011 to 2016 treated for AFs undergoing open reduction internal fixation (ORIF) and HFs (undergoing ORIF, hemiarthroplasty, or cephalomedullary nail). Outcome Measurements: Patient characteristics, comorbidities, functional status, acute complications, and mortality rates were recorded. Patients were matched 1:5 (AF:HF). Chi-square, Fisher exact, and Mann–Whitney U tests were used to compare groups, and multivariable logistic regression was used to compare the risk of complications or death while adjusting for relevant covariates. Results: A total of 303 AF patients (age: 78.2 ± 9.2 years/59.7% females/27.1% wall, 28.4% one column and 45.2% 2 columns ORIF) were matched to 1511 HF patients (age: 78.3 ± 9.1 years/60.2% females/37.2% hemiarthroplasty, 16.3% ORIF and 47.4% cephalomedullary nail). Length of stay (8.4 ± 7.1 vs. 6.4 ± 5.9 days) and time to surgery [(TS) 2.3 ± 1.8 versus 1.2 ± 1.4 days] were longer in the AF group ( P < 0.01). Unadjusted mortality rates were nonsignificantly higher for AFs versus HFs (6.6% vs. 4.6%, P = 0.14). After covariable adjustment, the risk of mortality was significantly higher for AFs versus HFs (odds ratio: 1.89, 95% confidence interval: 1.07–3.35). Conclusion: Geriatric AFs pose a significantly higher adjusted mortality risk when compared with HF patients. Strategies to mitigate risk factors in this population are warranted. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.